Existence and Stability for Stochastic Partial Differential Equations with Infinite Delay - Jing Cui; Litan Yan; Xichao Sun (Abstract and Applied Analysis)
We consider a class of neutral stochastic partial differential equations with infinite delay in real separable Hilbert spaces. We derive the existence and uniqueness of mild solutions under some local Carathéodory-type conditions and also exponential stability in mean square of mild solutions as well as its sample paths. Some known results are generalized and improved.